Unlocking Dabrafenib’s Potential: A Quality by Design (QBD) Journey to Enhance Permeation and Oral Bioavailability through Nanosponge Formulation - Konda Sri Chaya Reddy; Darna Bhikshapathi; Jaini Pavan Kumar (Brazilian Journal of Pharmaceutical Sciences)
Abstract This research aims to create dabrafenib (DBF)-loaded nanosponges (NSPs) using β-cyclodextrin (β-CD) and diphenyl carbonate (DPC) as linker to improve oral bioavailability. DBF-loaded β-CD NSPs were synthesized by finely adjusting the molar ratio of β-CD to DPC and optimizing the stirring rate and duration using design methodology. After being loaded with DBF, the produced β-CD NSPs were characterized in terms of particle size, zeta potential (Z.P), polydispersity index (PdI), and drug entrapment efficiency (E.E). Studies on compatibility were carried out with FTIR (Fourier Transform Infrared Spectroscopy) and DSC (Differential Scanning Calorimetry). Permeability, in vivo, and in vitro experiments were performed on the improved NSPs and the pure medication. After optimizing DBF-loaded β-CD NSPs, a formulation with a mean size of 158.0 ± 7.2 nm, PdI of 0.282 ± 0.0044, and E.E of 86.23 ± 2.45% was obtained, based on the assessments indicated earlier. Zeta sizer, SEM, spectrum analysis, in vitro release, and pharmacokinetic tests were among the other analyses that further validated the optimization. An area under the curve (AUC0-t) of 7.95-fold greater and a Cmax 7.356 times higher than those of the free drug was demonstrated by the optimized β-CD NSPs, which showed a notable boost. The use of DBF-loaded NSPs holds promise as an effective strategy for enhancing release and bioavailability in the treatment of melanoma.